Benchmark study and uncertainty assessment of numerical predictions of global wave loads on damaged ships. (1st February 2020) - Parunov, Joško; Ćorak, Maro; Guedes Soares, C.; Jafaryeganeh, H.; Kalske, Seppo; Lee, Yongwon; Liu, Shukui; Papanikolaou, Apostolos; Prentice, David; Prpić-Oršić, Jasna; Ruponen, Pekka; Vitali, Natalija
Abstract: Results are presented of a benchmark and uncertainty assessment study organised by the MARSTRUCT Virtual Institute on global linear wave loads on damaged ship. The study has two aims: to acquire valuable information regarding damage modelling in seakeeping analysis of damaged ships and to contribute to a rational approach for definition of the model uncertainty of linear seakeeping tools. Eight institutes participated in the benchmark, with six codes, representative of important linear seakeeping theories in use nowadays. The benchmark ship is the DTMB 5415 hull, with well documented and accessible data to perform seakeeping analysis and experimental results for motion and global wave loads. The uncertainty analysis is performed using the Frequency Independent Model Error as the uncertainty measure. The analysis is performed for vertical motions, vertical and horizontal global wave load components, and for torsional moments. Uncertainty measures of individual motion and load predictions are presented and compared. In addition, a comparative analysis of linear seakeeping theories is performed and the accuracy of the simplified methods used for the prediction of seakeeping of a damaged ship is assessed. Finally, recommendations are provided for efforts to improve modelling uncertainties in transfer functions of wave loads on damaged ships. Highlights: Results are presented of a benchmark and uncertainty assessment study on global linear wave loads on damaged ships. Seven institutes participated in the benchmark, with six codes, representative of the important linear seakeeping theories in use nowadays. Seven institutes participated, with six codes, representative of the important linear seakeeping theories in use. The uncertainty analysis is performed using the Frequency Independent Model Error as the uncertainty measure. Uncertainty measures of individual motion and load predictions are presented and compared.